Perancangan Hotspot Server Untuk User Authentication dan Limit Bandwidth Menggunakan Mikrotik RB941 (Studi Kasus: Usaha Bandwidth) - Ritonga, Iqbal Giffari; Sumarno, Sumarno; Gunawan, Indra; Nasution, Zulaini Masruro (Building of Informatics, Technology and Science (BITS), 2019)
The research was carried out on the Bandwidth Business on Sinta Pohan Street Pematangsiantar where there was a problem that customers who bought WiFi passwords told other people who were not customers and lagged at the same time when customers access the internet and small WiFi coverage. This problem can be overcome by Mikrotik RB941 which is configured Hotspot Server and adds an Access Point in the business area. The purpose of this study is to use the Hotspot Server function, namely User Authentication and Limit Bandwidth for the authentication process and the Access Point function to strengthen WiFi signal coverage.